2017
DOI: 10.1111/jcpt.12560
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of protocol-based pharmacotherapy management on anticoagulation with warfarin for patients with cardiovascular surgery

Abstract: Warfarin therapy based on our novel PBPM was clinically safe and resulted in significantly better anticoagulation control compared to conventional care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
0
10
0
3
Order By: Relevance
“…Several studies have reported the efficacy of the use of physician‐approved protocols by pharmacists in pharmaceutical care . Further, the introduction of standardised protocols has also been useful for preventing medication errors .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the efficacy of the use of physician‐approved protocols by pharmacists in pharmaceutical care . Further, the introduction of standardised protocols has also been useful for preventing medication errors .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the efficacy of the use of physician-approved protocols by pharmacists in pharmaceutical care. [11][12][13] Further, the introduction of standardised protocols has also been useful for preventing medication errors. 14,15 The present study clearly demonstrates that implementation of protocol-based management based on co-operation between physicians and pharmacists that consists of checking the criteria for administration of anticancer drugs was useful for reducing anticancer drug wastage after preparation.…”
Section: F I G U R E 3 Comparison Of the Percentage (A) And Cost (B) mentioning
confidence: 99%
“…Our findings demonstrated that implementation of pharmaceutical warfarin therapy management for patients with poor quality of anticoagulation was able to improve TTR values when compared to the TTR of the same patient 1 year before starting the follow-up with the pharmacist. The major differences of our study with previous that have already shown a significant improvement in coagulation therapy are: our study is composed of two phases (retrospective and prospective phases), rather than only retrospective analysis; these previous studies included general patients, whereas our study included only patients with unstable dose and poor quality of warfarin therapy (TTR < 50%); and they are randomized trials, whereas our study was performed by using paired comparisons (the subjects’ TTR were assessed and compared before and after pharmacist-driven warfarin therapy management, in a way that before receiving pharmacist-guidance the patients received warfarin traditional treatment by physicians) ( Saokaew et al, 2012 ; Verret et al, 2012 ; Katada et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…These agreements often allow the PCPh to assess, review, and modify drug therapy independently, allowing the pharmacist to practice at the highest level within licensure. Examples of potential targets for CPAs may include the management of pain, delirium, gastric acid secretion, antimicrobial prophylaxis, blood glucose, and anticoagulation based on previously reported outcomes …”
Section: Conclusion and Future Of Perioperative Clinical Pharmacymentioning
confidence: 99%
“…Examples of potential targets for CPAs may include the management of pain, delirium, gastric acid secretion, antimicrobial prophylaxis, blood glucose, and anticoagulation based on previously reported outcomes. 18,21,[56][57][58][59] Telemedicine-based clinician support systems, when applied to the…”
Section: Pharmacy Student Education In Perioperative Carementioning
confidence: 99%